Syndicalisme chrétien et démocratisation de l’entreprise en Belgique - Quentin Jouan (La Nouvelle Revue du Travail, 2015)
The paper uses a historical perspective to question the dialectic between law and labour, highlighting the crucial role that law has played in the self-management union movement that arose during the 1960s and 1970s. More specifically, it explains how and why Belgium’s CSC Confederation of Christian Trade Unions considered it so important to devise legal standards for governing the dissemination of economic and financial information in works councils, a stage they viewed as a prerequisite to the establishment of true workplace democracy. Union records are scrutinised to recount CSC’s demands and achievements in the three areas comprising economic and financial information: information per se; accounting standards; and company audits. These topics may seem colourless and highly technical but they mask a deep social debate, namely to what extent employees participate in their companies’ lives. Alongside of this, the article also attests to the power of tools such as quantified information.